Problems, Solutions, and Expectations: 6C Integration of 21 st Century Education into Learning Mathematics - Inganah, Siti; Darmayanti, Rani; Rizki, Nopia (Universitas PGRI Madiun, 2023)
21st century education requires the integration of six competencies (6C) into the classroom. Because it is important to equip students with better skills. This survey examines the problems faced by mathematics teachers in integrating 21st century pedagogic 6Cs into integrated mathematics skills, and solutions to overcome these problems. This qualitative study collected data through questionnaires from 15 mathematics teachers spread across eight different schools. As a result, low student motivation, difficulties in integrating several skills, difficulties in time management, lack of understanding of student concepts, and difficulties in making lesson plans, as well as limited teaching materials. To overcome this problem, we integrate ideas based on providing videos (it's much better if you use/design videos yourself to suit the characteristics and interests of students), group work, providing private discussion rooms by watshapp, providing short material summaries with narration so that language is easy for students to understand, use timers to manage time, and ask for references and exchanges. Make lesson plans with other teachers.